ANALYSIS OF THE LEVEL OF ACCESSIBILITY OF THE TRANSPORT INFRASTRUCTURE IN THE CITY AND WAYS TO IMPROVE IT - Никончук, Вікторія; Пашкевич, Світлана (SWorldJournal, 2025)
The article deals with the comprehensive study of the level of accessibility of the transport infrastructure in the city of Rivne, with a special emphasis on ensuring accessibility for low-mobility population groups, such as people with disabilities, elde